Responses of the Martian Magnetosphere to an Interplanetary Coronal Mass Ejection: MAVEN Observations and LatHyS Results. Issue 16 (17th August 2018) - Romanelli, N.; Modolo, R.; Leblanc, F.; Chaufray, J.‐Y.; Martinez, A.; Ma, Y.; Lee, C. O.; Luhmann, J. G.; Halekas, J.; Brain, D.; DiBraccio, G.; Espley, J.; et al.
Abstract: The Mars Atmosphere and Volatile EvolutioN (MAVEN) spacecraft observed a strong interplanetary coronal mass ejection (ICME) reaching Mars on 13 September 2017. In this work we analyze the interaction between such an extreme event and the Martian‐induced magnetosphere by means of Laboratoire Atmosphères, Milieux et Observations Spatiales Hybrid Simulation (LatHyS) stationary runs and magnetic field and plasma observations obtained by MAVEN in a time interval from ∼ 5 hr before the ICME shock arrival to about 5.5 hr after the impact. Detailed comparisons between simulation results and such MAVEN measurements are performed and show that several stages during this interaction can be described through a combination of steady states. LatHyS results show the simulated bow shock is closer to the planet for higher magnetosonic Mach number and solar wind dynamic pressure conditions, in agreement with previous observational studies. MAVEN observations and LatHyS results also suggest a compression on the flanks of the magnetic pileup boundary. Finally, simulated H + and O + planetary escape rates increase by a factor ∼10 and ∼2.4, respectively, due to the ICME passage through the Martian magnetosphere. Plain Language Summary: Studies on the responses of Mars to variable external conditions are of great importance, particularly to identify and characterize time‐dependent physical processes occurring inside and around its induced planetary magnetosphere. Solar extreme events are expected to play a fundamental role strongly modifying the plasma environment surrounding this atmospheric obstacle, lacking an intrinsic global magnetic field. In this work we analyze the interaction between an interplanetary coronal mass ejection and Mars by means of Mars Atmosphere and Volatile EvolutioN (MAVEN) magnetic field and plasma observations obtained around 13 September 2017. In addition, we study this interacting system by performing three Laboratoire Atmosphères, Milieux et Observations Spatiales Hybrid Simulation stationary runs. Detailed comparisons between simulation results and MAVEN measurements show that several stages during the analyzed time interval can be described through a combination of steady states. In addition, the simulated bow shock is found closer to the planet for higher magnetosonic Mach number and solar wind dynamic pressure conditions. MAVEN observations and Laboratoire Atmosphères, Milieux et Observations Spatiales Hybrid Simulation results also suggest a compression on the flanks of the magnetic pileup boundary. Finally, simulated H+ and O+ planetary escape rates are found to increase by a factor ∼10 and ∼2.4, respectively, due to the interplanetary coronal mass ejection passage through the Martian magnetosphere. Key Points: The interaction between an ICME and Mars is studied by means of MAVEN observations and LatHyS stationary runs A characterization of the bow shock compression during this event is performed, based on LatHyS results During the analyzed event, simulated H + and O + planetary loss rates increase by a factor ∼10 and ∼2.4, respectively